Buyer and consumer's portuguese "quality wine" behaviour - Duarte, M. F. (2010)
The main purpose of this paper is to present and discuss the results of a regional survey on buyer and consumer's behaviour. Results allow us to identify consuming buyer patterns and relate them to consumer's attitudes and caracteristics such as age, sex and educacional levels.They also suggest some important variables than can be used to differentiate portuguese "Quality Wines Produced in Specified Regions" (QWPSR) and are potencial material to develop satrategies, useful to the new "quality wine" regions, particulary giving references for a segmentation process or even for the creation of communicational plans for each region or brand. This set of co-ordinated information, allows a better assessment of the Portuguese consumer's preferences. The research tries also to determine and discuss the positioning of the Portuguese QWPSR, as well as the opportunities that may be used by wine makers, the threats they might eliminate and the usefulness of constructing a good marketing plan. This survey was conducted in the the so called Grande Lisboa, in 1996, and the data were treated by using market research statistical techniques.